Intravitreal bevacizumab for macular edema due to proton beam radiotherapy: Favorable results shown after eighteen months follow-up - Eleni Loukianou; Dimitrios Brouzas; Eleni Georgopoulou; et al (Dove Medical Press, 2010)
Eleni Loukianou, Dimitrios Brouzas, Eleni Georgopoulou, Chrysanthi Koutsandrea, Michael ApostolopoulosEye Department, University of Athens, Athens, GreecePurpose: To evaluate the safety and efficacy of intravitreal injections of bevacizumab (Avastin®) as a treatment option for radiation maculopathy secondary to proton beam radiotherapy for choroidal melanoma.Case: A 61-year-old woman presented with a gradual decrease in left eye visual acuity (VA) 29 months after proton beam radiotherapy for choroidal melanoma. On presentation, her best-corrected VA (BCVA) was 2/10 in the left eye and the intraocular pressure was 15 mmHg. Fundoscopy revealed cystoid macular edema, intraretinal hemorrhages, epiretinal membrane in the posterior pole, and residual tumor scar with exudative retinal detachment and hard exudates in the periphery of the superotemporal quadrant. A treatment with intravitreal injections of bevacizumab (Avastin®) was recommended. The injections were performed on a six-weekly basis.Results: The central retinal thickness prior to the treatment was 458 μm. After the first intravitreal injection of bevacizumab, the retinal thickness at the centre of the fovea was reduced to 322 μm. After the third injection, the central retinal thickness was 359 μm and 18 months after presentation, it reduced to 334 μm. The BCVA increased to 3/10 after the intravitreal injections of bevacizumab and remained stable during the follow-up period. The intraocular pressure was within normal range during the follow-up period.Conclusion: Bevacizumab should be regarded as a treatment option for macular edema due to proton beam radiotherapy for choroidal melanoma. By reducing the central retinal thickness, intravitreal bevacizumab can improve VA or ameliorate further decline caused by radiation maculopathy.Keywords: bevacizumab (Avastin®), choroidal melanoma, macular edema, radiation retinopathy